EMPOWERING WOMEN THROUGH UNIFORM CIVIL CODE: LEGAL AND SOCIAL DIMENSIONS - Garg, Megha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India is a secular state that is state does not have any religion of its own. All religion is equal for a state. Article 44 of Indian Constitution as a Directive principle of state policy provides that state shall secure to every citizen of India a uniform civil code. There are many civil laws such as C.P.C. 1909, Law of contracts, The Transfer of property act etc., but these are for personal matters such as marriage, divorce, inheritance, maintenance etc. communities are governed by their own personal laws. So, we can say UCC refers to personal laws. UCC is replacing the personal laws of major religion communities in India with common civil law. Concept of UCC is governed by the idea of gender justice and national integration. Women in India are still facing discrimination and inequality specially focused to the practices of Triple talaq and Halala etc. to protect the rights of women and to provide the gender equality. Voice has been raised many times for implementation of UCC, but UCC has been wrongly posited as an attack on religion. The demand of change in personal laws is essential as it would directly improve the status of women in many spheres like marriage, divorce, adoption, maintenance etc. But even after 69 years of independence, the implementation of UCC is just a distant dream. This paper is based on the implementation of UCC as a tool to provide religious harmony and to protect the rights of women and gender equality as given under our constitution of India.